2001
DOI: 10.1002/ajmg.1527
|View full text |Cite
|
Sign up to set email alerts
|

Parental attitudes toward a diagnosis in children with unidentified multiple congenital anomaly syndromes

Abstract: One of the most common and unsatisfying situations encountered in medical genetics clinics is the child with multiple congenital anomalies (MCAs) suggestive of an underlying syndrome for whom it is not possible to make a definitive diagnosis. We undertook a qualitative, descriptive study to learn more about the ways in which the lack of a diagnosis affects parental coping and adjustment to their child's special needs. Semistructured interviews were conducted with 29 parents of 16 children born with an unidenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
145
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(156 citation statements)
references
References 23 publications
10
145
0
1
Order By: Relevance
“…The concept and meanings of genetic cause, particularly of family associations are powerful tools for making sense of illness and negotiating blame (Nelkin & Lindee, 1995;Rosenthal et al, 2001;Hallowell et al, 2006;Arribas-Ayllon et al 2008). This article has demonstrated that this remains the case, even when a genetic syndrome is caused by a de novo deletion.…”
Section: Resultsmentioning
confidence: 99%
“…The concept and meanings of genetic cause, particularly of family associations are powerful tools for making sense of illness and negotiating blame (Nelkin & Lindee, 1995;Rosenthal et al, 2001;Hallowell et al, 2006;Arribas-Ayllon et al 2008). This article has demonstrated that this remains the case, even when a genetic syndrome is caused by a de novo deletion.…”
Section: Resultsmentioning
confidence: 99%
“…As previous data suggest [Clarke-Steffen, 1993a;Cohen, 1993;Rosenthal et al, 2001], some parents may be able to find hope in uncertainty and use this as an effective coping strategy. Studies that have used teaching interventions within the Transactional Model of Stress and Coping have reported significant improvements in coping efficacy, distress, and depression [Folkman et al, 1991;Chesney et al, 1996].…”
Section: Interventions Aimed At Minimizing Uncertainty By Highlightinmentioning
confidence: 87%
“…There is limited literature related to parents' experiences of living with a child with KS, or their experiences of arriving at and receiving a diagnosis. Despite preexisting research regarding the diagnostic process for a variety of other conditions, [19][20][21] there is limited research focusing specifically on parents' experiences of the diagnostic process of KS and its impact. Of the few published studies that do relate to KS, the focus was on a specific time point of diagnosis such as prenatally, 22 or studied more than one condition, such as all sex chromosome abnormalities.…”
Section: Introductionmentioning
confidence: 99%